Strategi Pengembangan Agroindustri Berbasis Usahatani Terpadu di Kecamatan Patampanua Kabupaten Pinrang - Hamsia; Andi Nuddin; Andi Sitti Halimah (Jurnal Galung Tropika, 2025)
Integrated farming-based agroindustry is a system for processing organic fertilizer that combines various agricultural activities, including crop farming, livestock, aquaculture, and other related sciences within a single land area that maintains an internal energy flow. This study aims to identify and describe farmers' perceptions of the use of liquid organic fertilizer and to formulate development strategies for integrated farming-based agroindustry in Pinrang Regency. The methods used in this research are qualitative descriptive analysis and Interpretative Structural Modeling (ISM). The results indicate that liquid organic fertilizer requires a more consistent application process and has a stronger odor compared to chemical fertilizers, leading many farmers to continue using chemical fertilizers. The ISM analysis identifies two primary strategies that are most effective for implementation: enhancing the role of agricultural extension workers and developing processing technology. These strategies involve intensive farmer engagement through regular field visits and training to facilitate technology adoption, as well as the provision of farming facilities and infrastructure as part of the technology development process introduced by extension agents.